Revitalisasi Konsep Gotong Royong dan Berakhlak Mulia dalam Profil Pelajar Pancasila Berbasis Nilai Al-Qur'an - Azis, Annisa Rahmania; Tamimi, Abdillah Rosyid (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2025)
This study explores the revitalization of the values of gotong royong (mutual cooperation) and noble character in the framework of strengthening the Pancasila Student Profile (P5) based on Qur'anic values. Amidst rapid social and technological transformations, traditional values such as solidarity and ethics are eroding. This research employs a literature study to analyze Qur'anic principles as foundational elements for character education in Indonesia's Merdeka Curriculum. The findings highlight that gotong royong fosters communal solidarity and empathy, rooted in Qur'anic teachings like QS. Al-Maidah 2, which emphasizes cooperation for virtue. Similarly, noble character, drawn from prophetic examples in QS. Al-Ahzab 21, underlines moral integrity, empathy, and social harmony. The integration of these values through P5 involves collaborative projects, daily behavioral reinforcement, and reflective practices. These initiatives cultivate students' intellectual, social, and spiritual balance, preparing them as socially responsible individuals. The study concludes with recommendations for systematic strategies to embed these values into educational curricula, ensuring a holistic approach to developing resilient and ethical youth.